The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1038/s41598-020-78604-8
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic composition and seasonal dynamics of the air microbiome in West Siberia

Abstract: Here, we describe taxonomical composition, as well as seasonal and diel dynamics of airborne microbial communities in West Siberia. A total of 78 airborne biomass samples from 39 time intervals were analysed, within a temperature range of 48 °C (26 °C to − 22 °C). We observed a 5–170-fold decrease in DNA yield extracted from the airborne biomass in winter compared to summer, nevertheless, yielding sufficient material for metagenomic analysis. The airborne microbial communities included Actinobacteria and Prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
1
4
0
1
Order By: Relevance
“…Our previous air microbiome studies ( 13–16 ) revealed the temporal and spatial dynamics of atmospheric microbial communities, particularly in a tropical setting ( 14 ). In addition, the recently observed phenomenon of the microbial community composition oscillating between day and night (diel cycle) has now been confirmed to also occur in temperate climates ( 15 , 16 ). In particular, the vertical stratification of airborne microorganisms in the lower troposphere was demonstrated above and below the planetary boundary layer ( 16 ).…”
Section: Introductionmentioning
confidence: 72%
“…Our previous air microbiome studies ( 13–16 ) revealed the temporal and spatial dynamics of atmospheric microbial communities, particularly in a tropical setting ( 14 ). In addition, the recently observed phenomenon of the microbial community composition oscillating between day and night (diel cycle) has now been confirmed to also occur in temperate climates ( 15 , 16 ). In particular, the vertical stratification of airborne microorganisms in the lower troposphere was demonstrated above and below the planetary boundary layer ( 16 ).…”
Section: Introductionmentioning
confidence: 72%
“…We would like to emphasize that studies of this type are a fundamental basis for identifying aspects of human–nature interactions, and in particular those related to the routes of disease transmission and potential impact on human health [ 57 ]. Nevertheless, only sporadic results of the metagenomic analysis of bioaerosols have been reported in Russia [ 58 ].…”
Section: Metagenomic Sequencingmentioning
confidence: 99%
“…Подчеркнем, что исследования такого типа являются фундаментальной основой для выявления аспектов взаимодействия человека с природой, в частности, касающихся способов передачи заболеваний и потенциального воздействия на здоровье человека [57]. Тем не менее, опубликованы только единичные результаты метагеномного анализа биоаэрозолей в России [58].…”
Section: метагеномное секвенированиеunclassified
“…A method frequently used to assess the airborne inoculum is the use of qPCRs (Clark et al, 2023), which can provide estimates of spore concentrations relatively quickly. The aerosol microbiome is known to have a complex relationship with temperature, relative humidity and rainfall (de Groot et al, 2021; Gusareva et al, 2020). Variation in airborne spores likely impacts the phyllosphere microbiome, as we would expect microbes present in the air to land on and colonize exposed plant tissues, potentially affecting disease risk.…”
Section: Introductionmentioning
confidence: 99%